Associations of HIV pre-exposure prophylaxis (PrEP) indication, HIV risk perception and unwillingness to use PrEP among people who inject drugs in Baltimore, MD - Tarfa Verinumbe; Gregory M. Lucas; Katie Zook; Brian Weir; Miles Landry; Kathleen R. Page; Susan G. Sherman; Oluwaseun Falade-Nwulia (Drug and Alcohol Dependence Reports)
Background: Perceived HIV risk may impact willingness to initiate PrEP among people who inject drugs (PWID). Methods: We analyzed baseline data from PrEP eligible PWID in Baltimore, MD. Risk perception was assessed by PWID relative to the average risk of their age group categorized as: higher-than, lower-than, or about average. Participants were informed of PrEP for HIV prevention and asked about their willingness to use daily PrEP. Associations of PrEP indication (categorized as injection risk only vs any sexual risk), perceived HIV risk and non-willingness to use PrEP was assessed using generalized linear models. Results: Among 489 participants, 61 % were male, 66 % were Black and mean age was 46 years. One-third (35 %) of the participants were aware of PrEP and <1 % had used PrEP in the prior 30 days. Overall, 30 % of PWID reported lower-than-average perceived HIV risk and 18 % reported non-willingness to use PrEP. Participants with injection risk only were more likely (aOR: 2.75; 95 %CI: 1.60 – 4.73) to report having lower-than-average perceived HIV risk compared to those with any sexual risk. Participants with lower-than-average perceived risk were more likely to report non-willingness to use PrEP compared to those with higher perceived risk (adjusted PR: 1.91; 95 %CI: 1.18 – 3.10). Conclusion: A considerable proportion of PWID eligible for PrEP reported having low risk of HIV acquisition despite being eligible for PrEP. Consistent and tailored PrEP messaging that addresses drug use HIV risk perception may be critical to increasing PrEP uptake among PWID.